INTERNATIONAL BRAND IMAGE DEVELOPMENT FOR MSMES: CASE OF LEGIT CRACKERS - Tunjungsari, Hetty Karunia; Ie, Mei; Utama, Didi Widya; Mawardi, Viny Christanti; Solikhah, Nafia; Yukianti, Chiara Rizka; Buana, Salsabila Ayunda Martsa (Graduate Program of Universitas Tarumanagara, 2023)
The growth of MSMEs drives Indonesia's economic growth in significant contribution. Businesses that are quite popular with MSMEs are businesses in the culinary sector. Legit Crackers is an MSME that produces snacks in the form of high quality and low-calorie mackerel fish crackers. Fish crackers are a popular snack among Indonesian people, with various types and various flavors. However, like many other MSME’s businesses, the fish cracker business also faces a number of problems that need to be overcome. One solution is to develop product formulas and brand images. This is important because good product quality can influence the awareness, trust and confidence of potential buyers. For Legit Crackers, a low-calorie snack business that was founded in 2017, building a brand image is a challenge. To increase marketing potential, good quality and unique product development, packaging and promotions are carried out. Development of a comprehensive strategic plan to overcome production efficiency problems, improve business image, and open access to international markets. This research aimed to innovate and develop market potential for low-calorie snack products. It is hoped that this will improve consumer brand image towards Legit Crackers, develop the low-calorie snack market potential and penetrate the global market.